CATALYTIC HYDROCRACKING OF WASTE LUBRICANT OIL INTO LIQUID FUEL FRACTION USING ZnO, Nb2O5, ACTIVATED NATURAL ZEOLITE AND THEIR MODIFICATION - Wega Trisunaryanti; Suryo Purwono; Arista Putranto (Indonesian Journal of Chemistry, 2008)
Catalytic hydrocracking of waste lubricant oil into liquid fuel fraction using ZnO, Nb2O5, activated natural zeolite (ZAAH) and their modification has been investigated. The zeolite was produced in Wonosari, Yogyakarta. Activation of the zeolite was carried out by refluxing with HCl 3M for 30 min, produced the activated natural zeolite (ZAAH). The ZnO/ZAAH catalyst was prepared by impregnation of Zn onto the ZAAH by ion exchange method using salt precursor of Zn(NO3)2.4H2O. The Nb2O5/ZAAH catalyst was prepared by mixing the ZAAH sample with Nb2O5 and oxalic acid solution until the paste was formed. The impregnation of Zn onto Nb2O5/ZAAH was carried out using the same method to that of the ZnO/ZAAH catalyst resulted ZnO/Nb2O5-ZAAH catalyst. Characterization of catalyst includes determination of Zn metal by Atomic Absorption Spectroscopy (AAS), acidity by gravimetric method and catalyst porosity by Surface Area Analyzer (NOVA-1000). Catalytic hydrocracking was carried out in a semi-batch reactor system using ZnO, ZAAH, ZnO/ZAAH and ZnO/Nb2O5-ZAAH catalysts at 450 oC under the H2 flow rate of 15 mL/min. and the ratio of catalyst/feed = 1/5. The composition of liquid products was analyzed by Gas Chromatograpy (GC).The results showed that impregnation of ZnO and/or Nb2O5 on the ZAAH increased the acidity and specific surface area of catalyst. The products of the hydrocracking process were liquid, coke and gas. Conversion of liquid products was increased by the increase of catalyst acidity. The highest liquid product was produced by ZnO/Nb2O5-ZAAH catalyst, 52.97 wt-%, consist of gasoline, 38.87 wt-% and diesel, 14.10 wt-%.